Culture Analysis Of Poverty In Fisherman Families Case Study Of Nagari Ranah Panantian, Sungai Beremas District, Pasaman Barat District - Riska Hafiza (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
Artikel Penelitian segera ditindaklanjutkan dan mohon diterbitkan. Terimakasih